1997
DOI: 10.1021/jo970677d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence of Through-Space Electrostatic Stabilization of the Incipient Oxocarbenium Ion by an Axially Oriented Electronegative Substituent During Glycopyranoside Acetolysis

Abstract: The rate of acetolysis of methyl 2,3,6-tri-O-methyl-R-D-galacto-and -glucopyranosides depends strongly on the electronegativity of the C4 substituent. Thus, of the three derivatives studied (4methoxy, 4-acetoxy, and 4-acetamido-4-deoxy derivatives of D-galacto-and D-glucopyranosides), the glycopyranosides bearing the most electronegative C4 substituent (methoxy group) acetolyze at the fastest rate, whereas those having the least electronegative C4 substituent (N-acetamido group) acetolyze at the slowest rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
117
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 18 publications
23
117
1
Order By: Relevance
“…These findings are in agreement with the findings of Miljkovic et al [29,30] who studied the acetolysis of methyl 2,3,4,6-tetra-O-methyl-α-and β-D-gluco-and galactopyranosides and found that α-D-galactopyranoside acetolyzed ca. 20 times faster than α-D-glucopyranoside.…”
Section: Stereoelectronic Effects Of Substituents: Polyhydroxylated Psupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with the findings of Miljkovic et al [29,30] who studied the acetolysis of methyl 2,3,4,6-tetra-O-methyl-α-and β-D-gluco-and galactopyranosides and found that α-D-galactopyranoside acetolyzed ca. 20 times faster than α-D-glucopyranoside.…”
Section: Stereoelectronic Effects Of Substituents: Polyhydroxylated Psupporting
confidence: 93%
“…20 times faster than α-D-glucopyranoside. The influence of the electronegativity of the C4 substituent upon the rate of acetolysis was examined [30] by comparing the C4-OCH 3 with the C4-OAc and C4-NHAc substituent (see also Chap. 3).…”
Section: Stereoelectronic Effects Of Substituents: Polyhydroxylated Pmentioning
confidence: 99%
“…The higher reactivity of galactosides in comparison with glucosides has also been reported. 25,31,32 The higher reactivity of galactose might be explained by assuming that the formation of an oxonium intermediate is the rate-determining step in these reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Such an intermediate is commonly observed in the hydrolysis of glycans. [52][53][54][55] Moreover, using undamaged 2ʹ-deoxyuridine and 2ʹ-deoxycytidine, clear evidence was obtained that the N-glycosidic bond hydrolysis is mediated by the oxocarbenium ion pathway. 13 Although there were data supporting the involvement of a Schiff base intermediate resulting from the rupture of C1ʹ-O4ʹ bond (Route B, Figure 1), 11,12 such a route is not considered to contribute to the deglycosylation process.…”
Section: Discussionmentioning
confidence: 99%